Bear stays up for Christmas - Wilson, Karma (Wilson, Karma. Bear and his friends., 2004)
Bear's friends awaken him the day before Christmas and help him to stay awake as they bake fruitcakes, fill stockings, and sing carols; then, while they sleep, he prepares his own surprise.